Doing memory work with older men: the practicalities, the process, the potential. Issue 4 (12th December 2016) - Blake, Vic; Hearn, Jeff; Barber, Randy; Jackson, David; Johnson, Richard; Luczynski, Zbyszek
Abstract : Purpose: The purpose of this paper is to describe the process of setting up and participating in a collective memory work group of older men, with a focus on the making and unmaking of older men and masculinities through age, ageing, gender, gendering, and other intersections. Design/methodology/approach: Participant review and reflection on collective of memory work group of older men. Findings: Memory work is located in relation to related but different forms of writing and group work, emphasizing how in this method everyone becomes a writer, an author, a listener, a reader, a discussant, and a commentator. This provides a novel way to explore the constructions and intersections of ageing, gender, men, and masculinities. Social implications: The potential of memory work, both for working with older men, and more generally is outlined. Key issues are: genuine and collective commitment to substantive change, not just at a personal level, but also at wider social/political/cultural levels; willingness to trust in the other members of the group, an issue that may be difficult for some men; and commitment for caring for one another especially in their moments of greatest vulnerability. Originality/value: There is little, if any, other writing on this approach to ageing, men, and masculinities. The paper is therefore of great value, and may stimulate wider application of this approach.